Household beliefs about malaria testing and treatment in Western Kenya: the role of health worker adherence to malaria test results - Saran, Indrani (Malar J, 2017)
BACKGROUND: Although use of malaria diagnostic tests has increased in recent years, health workers often prescribe anti-malarial drugs to individuals who test negative for malaria. This study investigates how health worker adherence to malaria case management guidelines influences individuals’ beliefs about whether their illness was malaria, and their confidence in the effectiveness of artemisinin-based combination therapy (ACT). METHODS: A survey was conducted with 2065 households in Western Kenya about a household member’s treatment actions for a recent febrile illness. The survey also elicited the individual’s (or their caregiver’s) beliefs about the illness and about malaria testing and treatment. Logistic regressions were used to test the association between these beliefs and whether the health worker adhered to malaria testing and treatment guidelines. RESULTS: Of the 1070 individuals who visited a formal health facility during their illness, 82% were tested for malaria. ACT rates for malaria-positive and negative individuals were 89 and 49%, respectively. Overall, 65% of individuals/caregivers believed that the illness was “very likely” malaria. Individuals/caregivers had higher odds of saying that the illness was “very likely” malaria when the individual was treated with ACT, and this was the case both among individuals not tested for malaria [adjusted odds ratio (AOR) 3.42, 95% confidence interval (CI) [1.65 7.10], P = 0.001] and among individuals tested for malaria, regardless of their test result. In addition, 72% of ACT-takers said the drug was “very likely” effective in treating malaria. However, malaria-negative individuals who were treated with ACT had lower odds of saying that the drugs were “very likely” effective than ACT-takers who were not tested or who tested positive for malaria (AOR 0.29, 95% CI [0.13 0.63], P = 0.002). CONCLUSION: Individuals/caregivers were more likely to believe that the illness was malaria when the patient was treated with ACT, regardless of their test result. Moreover, malaria-negative individuals treated with ACT had lower confidence in the drug than other individuals who took ACT. These results suggest that ensuring health worker adherence to malaria case management guidelines will not only improve ACT targeting, but may also increase patient/caregivers’ confidence in malaria testing and treatment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12936-017-1993-7) contains supplementary material, which is available to authorized users.